2015
DOI: 10.1016/j.plaphy.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Using the quantum yields of photosystem II and the rate of net photosynthesis to monitor high irradiance and temperature stress in chrysanthemum (Dendranthema grandiflora)

Abstract: Using the quantum yields of photosystem II and the rate of net photosynthesis to monitor high irradiance and temperature stress in chrysanthemum (Dendranthema grandiflora). Plant physiology and biochemistry (Paris), 90,(14)(15)(16)(17)(18)(19)(20)(21)(22)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
2
27
0
2
Order By: Relevance
“…Saturating pulses were applied at 20 s intervals to measure the maximum fluorescence yield during actinic illumination (F # m ) as well as the chlorophyll fluorescence yield during actinic illumination (F # ). NPQ was calculated according to the following formula: (Janka et al, 2015;Yang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Saturating pulses were applied at 20 s intervals to measure the maximum fluorescence yield during actinic illumination (F # m ) as well as the chlorophyll fluorescence yield during actinic illumination (F # ). NPQ was calculated according to the following formula: (Janka et al, 2015;Yang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown increased PSII thermotolerance under drought conditions (Oukarroum et al , Snider et al ), whereas others have shown increased PSII sensitivity to heat (Jiang and Huang , Tozzi et al ). The combination of high temperatures with high levels of light has also been shown to promote PSII inhibition (Janka et al ), whereas some studies have found that high levels of light could promote PSII thermotolerance (Georgieva et al ). These examples highlight the complexity of stress interaction and the need for further studies on the mechanisms involved in plant photosynthetic response to combined environmental constraints.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is not limited to vertical farms, but can be used in greenhouses as well, applying supplemental light only as needed. This may be especially beneficial under conditions with fluctuating PPFD from sun light (e.g., in greenhouses), which results in fluctuating F PSII (Janka et al, 2015) and ETR. The biofeedback system can automatically adjust the supplemental light levels to assure that ETR is maintained at or above a specific minimum threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Because chlorophyll fluorescence is relatively easy to measure and provides detailed physiological information, such measurements can be a valuable tool to optimize greenhouse production (Baker and Rosenqvist, 2004) and to monitor crop responses to light (Pocock, 2015). For example, Janka et al (2015) used chlorophyll fluorescence measurements to monitor diurnal and dynamic fluctuations in F PSII of greenhouse crops. Our objective was to develop a biofeedback system that not only monitors F PSII and ETR, but that can also control the PPFD from LED lights to maintain a specific ETR.…”
mentioning
confidence: 99%